MEMPERKENALKAN METODE INVESTIGASI PEMECAHAN MASALAH UNTUK ANAK SEKOLAH DASAR MELALUI SERIAL ANIME JEPANG DETECTIVE CONAN - Juli Loisiana Butar-Butar; Indah Simamora (JURNAL CURERE, 2022)
This study aims to introduce an investigation method to solve mathematical problems using the Japanese anime series Detective Conan, while the spesific purpose is to introduce students to problem solving method that they need to understand based on the information provided and manage the information based on their abilities.  The method used in this research is classroom action research by showing one episode of the Detective Conan anime, after that organized several groups to test each group could solve the challenge quiz within 30 minutes and the results of the analysis of work based on cognitive function. The results showed that the mean duration of group investigation quiz was not significantly different from 30 minutes. In addition, based on the mean assessment of the results of the work there are two results, namely there are differences in values based on groups and no differences in values based on cognitive function..